Agness Mseteka: Maternity Waiting Home Caretaker and Protector of Pregnant Women in Rural Zambia - Julie M. Buser; Brenda Moyo (Ubiquity Press, 2021)
To share her story, we interviewed Agness Mseteka about her experience as a maternity waiting home (MWH) caretaker at the district hospital in rural Lundazi, Zambia. Maternity waiting homes, also known as mother's shelters, are structures built near healthcare facilities to minimize the critical barrier of distance to accessing maternal health services. Agness' story highlights the central role caretakers play in contributing to the successful implementation and sustainability of MWH interventions. Agness is well positioned to be an agent of positive change by bringing health education to pregnant women. An important lesson learned from Agness' story is the need for future research to explore the sustainability of MWHs and long-term effectiveness of income generating activities by the community after the completion of externally funded implementing programs.